Estimating willingness to pay for Wetland conservation: a contingent valuation study of Paya Indah Wetland, Selangor Malaysia - Mei, Kuang Siew; Yacob, Mohd Rusli; Radam, Alias; Adamu, Abdullahi; Alias, Emmy Farha (Elsevier, 2015)
The objective of this study is to estimate the visitors’ willingness to pay (WTP) for conservation of Paya Indah Wetlands (PIW) using Contingent Valuation Method (CVM). Respondents were randomly selected for data collection through face-to-face interview. A logit model was used to estimate the visitors’ WTP entrance fee to PIW. The study results indicated that visitors’ level of income and bid price were the significant factors influencing visitors’ WTP. The mean WTP amount obtained was RM 7.12 per visitor. The findings also showed that the expected benefit of conservation program in PIW was estimated at RM 630,768 in 2012